Initial experience with EUS-guided Tru-cut biopsy of benign liver disease - DeWitt, John; McGreevy, Kathleen; Cummings, Oscar; Sherman, Stuart; LeBlanc, Julia K.; McHenry, Lee; Al-Haddad, Mohammad; Chalasani, Naga (Gastrointestinal endoscopy, 2009)
Histologic biopsy of the liver is often essential for diagnosing hepatic parenchymal disease. Tissue acquisition is traditionally obtained by a surgical, transvascular, or percutaneous route. To describe our initial experience with EUS-guided Tru-cut biopsy (EUS-TCB) of benign liver disease. A prospective case series. A tertiary-referral hospital in Indianapolis, Indiana. Consecutive subjects undergoing EUS with suspected hepatic parenchymal disease. EUS-TCB of the liver. Liver biopsy specimen yield, diagnosis, and procedural complications. Specimens were routinely stained with hematoxylin and eosin and with special stains for reticulin, iron, and trichome. Each case was reviewed by a single experienced pathologist for the number of portal spaces, total specimen length, and final diagnosis. An adequate specimen was defined as 6 or more complete portal tracts. Between February 2007 and March 2008, 21 consecutive patients (mean age 45 years; 13 women) were evaluated. The most common indications for liver biopsy were suspected nonalcoholic steatohepatitis (n = 9), intrahepatic cholestasis (n = 4), and suspected cirrhosis (n = 3). Transgastric biopsy (median 3 passes, range 1-4) into the left lobe (n = 18) or both the left and caudate lobe (n = 3) yielded a median total specimen length of 9 mm (range 1-23 mm). The median total number of portal tracts in the specimen was 2 complete (range 0-10) plus 3 partial (range 0-8) tracts. Six or more complete portal tracts were present in 6 of 21 (29%). A histologic diagnosis was obtained in 19 of 21 (90%). There were no complications. The small sample size and low-risk population. In our initial experience, transgastric EUS-TCB of suspected benign liver disease by using a 19-gauge needle appears safe and feasible. Samples obtained are usually smaller than those traditionally considered adequate for histologic assessment. Further refinement of this technique appears indicated.